Theoretical Background of Competitiveness Index Determination in Regions - Dymchenko, Olena; Beliavtseva, Victoria; Rudachenko, Olha; Tararuev, Yurii (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
It is determined in the article, development and implementation of methods to justify management decisions to be essential when concerning the increase of competitiveness and investment attractiveness of the regions. Based on the European and local experience in the regions rate determination analysis, the basic principles and stages of calculating the regional rating were formed. The index numbers included in the rating are characterized and the necessity of their use is justified. The calculation procedure and method of the regions index of competitiveness is offered